Current challenges and benefits of teaching World Englishes - Refanja Rahmatillah; Endah Anisa Rahma; Ana Elvia Jakfar; Giovanni Oktavinanda (Universitas Merdeka Malang, 2022)
The existence of multi varieties of English in today’s international communication requires the inclusion of what is called World Englishes (WE) in English teaching. While many have attempted to incorporate WE in English classrooms, such clear procedures on how to implement this along with the outcomes are so far hard to find. Therefore, this review elaborates on the implementation of WE, examines the challenges, and highlights the benefits of this incorporation. 18 research articles from the year 2010 to 2019 on the incorporation of WE worldwide starting from school to university context were reviewed. The review reveals that the teaching of WE is mostly still in the introduction phase since a majority of English teachers and learners still prefer the native English varieties. On the other hand, the introduction of WE to English learners may improve their confidence to use English. This review is expected to be able to provide clear current conditions of WE teaching, impose challenges that need to be addressed, and at the same time encourage the incorporation of WE in an English classroom.DOI: 10/26905/enjourme.v7i1/7827